High-transmittance self-cleaning coated glass and preparation method thereof
By spin-coating a high-transmissive coating solution on the glass substrate and forming a micro-nano structure array, the problem that existing glasses are difficult to meet the good light transmittance and self-cleaning ability at the same time is solved, and the high light transmittance and self-cleaning effect are improved.
Patent Information
- Application Number
- CN202411824562.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-18
AI Technical Summary
Existing glasses are difficult to meet the requirements of good light transmittance and self-cleaning ability at the same time.
Using highly transparent coating glass, a high-transmissive coating solution including components such as magnesium fluoride, zinc fluoride, titanium dioxide and zinc salt is spin-coated onto the glass substrate, and a micro-nanostructure array is formed by laser etching.
It improves the light transmittance and self-cleaning effect of the glass, reduces the reflected light intensity on the glass surface, and enhances the chemical stability and durability of the glass.
Smart Images

Figure BDA0005183917180000111 
Figure BDA0005183917180000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional glass, and in particular relates to a high-transmittance self-cleaning coated glass and a preparation method thereof. Background Art
[0002] Self-cleaning glass refers to a type of glass on which pollutants or dust on the surface of ordinary glass can automatically fall off or be degraded under the action of gravity or external forces such as rain and wind, and can keep itself clean and maintain a beautiful surface under natural conditions.
[0003] As a building and decorative material, glass has been widely used in modern construction, household appliances, furniture and other fields due to its significant functions such as transparency, windproof, waterproof and anti-corrosion. With the continuous development of global science and technology and industry, environmental pollution problems are becoming increasingly serious, the dust content in the air is increasing, and the glass surface is easily covered with dust and dirt, losing its original characteristics. With the increasing proportion of glass curtain walls in the construction industry, the cleaning and care of glass curtain walls has become more and more prominent. The traditional manual mechanical cleaning and detergent wetting cleaning methods are not only uneconomical but also have safety hazards, and it is difficult to meet the needs of actual conditions. The development of the economy and society has led to the continuous improvement of people's requirements for the quality of life and the continuous enhancement of environmental protection and energy-saving awareness. People urgently need a new type of glass that has environmental protection effects, uses natural conditions to achieve automatic cleaning effects, and can beautify the environment to replace traditional glass. The emergence of self-cleaning glass just meets this demand of people. This not only brings convenience to daily life, but more importantly, it reduces the insecurity of high-altitude glass cleaning to a certain extent.
[0004] The existing technology mostly adopts the method of coating a special coating on the surface of the glass substrate to achieve the purpose of self-cleaning of the glass, but the coating will cause the light transmission performance of the glass to deteriorate, thus affecting the lighting. Therefore, how to ensure good lighting performance while achieving the purpose of self-cleaning is a major difficulty in the existing glass production. Summary of the invention
[0005] In view of the above-mentioned prior art, the present invention provides a high-transmittance self-cleaning coated glass and a preparation method thereof, so as to solve the technical problem that the existing glass is difficult to simultaneously meet the requirements of good light transmittance and self-cleaning ability.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is to provide a high-transmittance self-cleaning coated glass, including a glass substrate and a high-transmittance coating attached to the surface of the glass substrate; the high-transmittance coating is obtained by the following steps:
[0007] S1: Prepare a high-transmittance coating solution, which includes the following components in parts by weight:
[0008] 10-15 parts of magnesium fluoride powder, 2-4 parts of titanium dioxide powder, 0.5-2 parts of zinc fluoride powder, 1-3 parts of zinc salt, 0.2-1 parts of silicate, 0.5-2 parts of polyethylene glycol and 100 parts of solvent;
[0009] S2: Spin coating the high-transmittance coating liquid onto the cleaned glass substrate surface by spin coating, with the spin coating speed being 800-1000 rpm; and then vacuum drying to obtain a high-transmittance coating with a thickness of 100-300 nm;
[0010] S3: A micro-nano structure array is formed on the surface of the high-transmittance coating by using a laser etching process; the shape of the micro-nano structure is a pyramid, terrace or cone.
[0011] Based on the above technical solution, the present invention can also be improved as follows.
[0012] Furthermore, the glass substrate is commercially available silicate glass or commercially available borosilicate glass, and has a thickness of 0.5 to 2 cm.
[0013] Furthermore, the high-transmittance coating solution includes the following components in parts by mass:
[0014] 12 parts of magnesium fluoride powder, 3 parts of titanium dioxide powder, 1 part of zinc fluoride powder, 2 parts of zinc salt, 0.5 parts of silicate, 1 part of polyethylene glycol and 100 parts of solvent.
[0015] Furthermore, the preparation of the high-transmittance coating solution includes the following steps: adding a formulated amount of magnesium fluoride powder, titanium dioxide powder, zinc fluoride powder, zinc salt, silicate and polyethylene glycol to a solvent, and stirring for 30 to 60 minutes to obtain the solution.
[0016] Furthermore, the particle sizes of the magnesium fluoride powder, the titanium dioxide powder and the zinc fluoride powder are all less than 100 nm.
[0017] Furthermore, the silicate is sodium silicate or potassium silicate; the zinc salt is zinc nitrate or zinc chloride; and the solvent is an ethanol solution with a volume fraction of 70%.
[0018] Furthermore, in S2, the spin coating speed is 850 rpm; the vacuum drying temperature is 180-220° C., and the drying time is 30-60 min.
[0019] Furthermore, the laser energy density of laser etching in S3 is 15-30 J / cm 2 , the repetition frequency is 500-700f / kHz, and the number of scans is 15-30 times.
[0020] Furthermore, the spacing between adjacent micro-nano structures in the micro-nano structure array is 100-200 nm, and the height of the micro-nano structure is 50-200 nm.
[0021] The present invention also discloses a method for preparing the above-mentioned high-transmittance self-cleaning coated glass, comprising the following steps:
[0022] (1) Cleaning the glass substrate;
[0023] (2) preparing a high-transmittance coating liquid, and applying the high-transmittance coating liquid to the surface of the cleaned glass substrate by spin coating; and then vacuum drying to obtain a high-transmittance coating with a thickness of 100 to 300 nm;
[0024] (3) A micro-nano structure array is formed on the surface of the high-transmittance coating using a laser etching process.
[0025] The beneficial effects of the present invention are:
[0026] 1. The present invention coats a high-transmittance coating with a special composition on the surface of the glass substrate, which can effectively reduce the reflection of light by the glass and allow most of the light to pass through the glass, thereby improving the light transmittance of the glass. The components of the high-transmittance coating in the present invention include magnesium fluoride, titanium dioxide, zinc fluoride and zinc salt. Magnesium fluoride, titanium dioxide and zinc fluoride all have a high refractive index, which can effectively reduce the reflection of light. When light enters the glass from the air, the light will be reflected on the upper and lower interfaces of the high-transmittance coating. The reflected light on the two interfaces will interfere with each other, thereby reducing the intensity of the reflected light. The reduction in reflected light means an increase in transmitted light, so the light transmittance of the glass is improved. In addition, the magnesium fluoride in the high-transmittance coating also has excellent properties such as good thermal stability, high mechanical strength and high laser damage threshold. These properties enable the high-transmittance coating to be used not only as an anti-reflection film, but also as a protective film to increase the chemical stability and durability of the glass.
[0027] 2. The high-transmittance coating surface of the present invention has a micro-nano structure array, which forms tiny concave-convex structures on the glass surface. These structures can effectively break the regularity of the reflected light and cause the reflected light to be diffusely reflected, thereby reducing the intensity of the reflected light. In this way, more light can enter the interior of the glass, thereby improving the light transmittance of the glass; in addition, the micro-nano array structure not only changes the physical form of the glass surface, but also increases the propagation path of the light inside the glass. The presence of the micro-nano array causes the light to be reflected and refracted multiple times inside the glass, which helps the light to pass through the glass more fully and reduces the loss of light during the propagation process, thereby improving the light transmittance of the glass.
[0028] 3. The high-transmittance coating of the present invention contains titanium dioxide and zinc salt. Titanium dioxide can stimulate strong oxidizing ability under light irradiation, thereby decomposing pollutants such as organic matter and bacteria attached to the glass surface; while zinc salt can continuously release zinc ions. Zinc ions have excellent bactericidal effects and can work together with titanium dioxide to decompose bacteria and organic matter attached to the glass surface, thereby achieving the purpose of self-cleaning of the glass.
[0029] 4. The coated glass surface of the present invention has a micro-nano array, which can not only improve the light transmittance of the glass, but also effectively improve the surface properties of the glass, so that dust, organic pollutants, etc. are automatically separated from the glass surface under the scouring of rainwater, thereby improving the self-cleaning effect of the glass. DETAILED DESCRIPTION
[0030] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.
[0031] Embodiment 1:
[0032] A high-transmittance self-cleaning coated glass comprises a glass substrate and a high-transmittance coated film attached to the surface of the glass substrate; wherein the glass substrate is commercially available silicate glass with a thickness of 1 cm.
[0033] The high-transmittance self-cleaning coated glass in this embodiment is prepared by the following steps:
[0034] (1) The glass substrate was rinsed with acetone and anhydrous ethanol in sequence, then rinsed with clean water, and then dried at room temperature;
[0035] (2) Adding magnesium fluoride powder (≤100 nm), titanium dioxide powder (≤100 nm), zinc fluoride powder (≤100 nm), zinc nitrate, sodium silicate and polyethylene glycol (PEG-400) in a formula amount to a 70% ethanol solution, stirring at a speed of 500 rpm for 45 min at room temperature to obtain a high-transmittance coating solution; the components in the high-transmittance coating solution include, by mass:
[0036] 12 parts of magnesium fluoride powder, 3 parts of titanium dioxide powder, 1 part of zinc fluoride powder, 2 parts of zinc nitrate, 0.5 parts of sodium silicate, 1 part of polyethylene glycol (PEG-400) and 100 parts of 70% by volume ethanol solution;
[0037] (3) Spin coating the high-transmittance coating liquid onto the cleaned glass substrate surface at a spin coating speed of 850 rpm; then vacuum drying at 200° C. for 45 min to obtain a high-transmittance coating with a thickness of 200 nm;
[0038] (4) A micro-nanostructure array is formed on the surface of the high-transmittance coating by laser etching process; the laser energy density of the laser etching is 20 J / cm 2 , the repetition frequency is 600f / kHz, and the number of scans is 20 times; the shape of the micro-nanostructure in the micro-nanostructure array is pyramid-shaped, with a bottom side length of 100nm, a height of 100nm, and a spacing between adjacent micro-nanostructures of 200nm.
[0039] Embodiment 2:
[0040] A high-transmittance self-cleaning coated glass comprises a glass substrate and a high-transmittance coated film attached to the surface of the glass substrate; wherein the glass substrate is commercially available borosilicate glass with a thickness of 2 cm.
[0041] The high-transmittance self-cleaning coated glass in this embodiment is prepared by the following steps:
[0042] (1) The glass substrate was rinsed with acetone and anhydrous ethanol in sequence, then rinsed with clean water, and then dried at room temperature;
[0043] (2) Adding the formulated amount of magnesium fluoride powder (≤100 nm), titanium dioxide powder (≤100 nm), zinc fluoride powder (≤100 nm), zinc nitrate, sodium silicate and polyethylene glycol (PEG-400) to a 70% ethanol solution by volume, stirring at a speed of 500 rpm for 30 min at room temperature to obtain a high-transmittance coating solution; the components in the high-transmittance coating solution include, by mass:
[0044] 10 parts of magnesium fluoride powder, 4 parts of titanium dioxide powder, 0.5 parts of zinc fluoride powder, 3 parts of zinc chloride, 0.2 parts of potassium silicate, 2 parts of polyethylene glycol (PEG-400) and 100 parts of 70% by volume ethanol solution;
[0045] (3) Spin coating the high-transmittance coating liquid onto the cleaned glass substrate surface at a spin coating speed of 1000 rpm; then vacuum drying at a temperature of 180° C. for 60 min to obtain a high-transmittance coating with a thickness of 100 nm;
[0046] (4) A micro-nanostructure array is formed on the surface of the high-transmittance coating by laser etching process; the laser energy density of the laser etching is 15 J / cm 2 , the repetition frequency is 500f / kHz, and the number of scans is 30 times; the shape of the micro-nanostructure in the micro-nanostructure array is conical, with a bottom diameter of 100nm, a height of 200nm, and a spacing between adjacent micro-nanostructures of 100nm.
[0047] Embodiment 3:
[0048] A high-transmittance self-cleaning coated glass comprises a glass substrate and a high-transmittance coated film attached to the surface of the glass substrate; wherein the glass substrate is commercially available borosilicate glass with a thickness of 1 cm.
[0049] The high-transmittance self-cleaning coated glass in this embodiment is prepared by the following steps:
[0050] (1) The glass substrate was rinsed with acetone and anhydrous ethanol in sequence, then rinsed with clean water, and then dried at room temperature;
[0051] (2) Adding the formulated amount of magnesium fluoride powder (≤100 nm), titanium dioxide powder (≤100 nm), zinc fluoride powder (≤100 nm), zinc nitrate, sodium silicate and polyethylene glycol (PEG-400) to a 70% ethanol solution by volume, stirring at a speed of 500 rpm for 60 min at room temperature to obtain a high-transmittance coating solution; the components in the high-transmittance coating solution include, by mass:
[0052] 12 parts of magnesium fluoride powder, 2 parts of titanium dioxide powder, 2 parts of zinc fluoride powder, 1 part of zinc nitrate, 1 part of sodium silicate, 0.5 parts of polyethylene glycol (PEG-400) and 100 parts of 70% by volume ethanol solution;
[0053] (3) Spin coating the high-transmittance coating liquid onto the cleaned glass substrate surface at a spin coating speed of 800 rpm; then vacuum drying at a temperature of 220° C. for 30 min to obtain a high-transmittance coating with a thickness of 200 nm;
[0054] (4) A micro-nanostructure array is formed on the surface of the high-transmittance coating by laser etching process; the laser energy density of the laser etching is 30 J / cm 2 , the repetition frequency is 700f / kHz, and the number of scans is 15 times; the shape of the micro-nanostructure in the micro-nanostructure array is terraced, with a bottom side length of 100nm, a top side length of 50nm, a height of 50nm, and a spacing of 200nm between adjacent micro-nanostructures.
[0055] Comparative Example 1:
[0056] A high-transmittance self-cleaning coated glass comprises a glass substrate and a high-transmittance coated film attached to the surface of the glass substrate; wherein the glass substrate is commercially available silicate glass with a thickness of 1 cm.
[0057] The high-transmittance self-cleaning coated glass in this comparative example is prepared by the following steps:
[0058] (1) The glass substrate was rinsed with acetone and anhydrous ethanol in sequence, then rinsed with clean water, and then dried at room temperature;
[0059] (2) Adding magnesium fluoride powder (≤100 nm), titanium dioxide powder (≤100 nm), zinc fluoride powder (≤100 nm), zinc nitrate, sodium silicate and polyethylene glycol (PEG-400) in a formula amount to a 70% ethanol solution, stirring at a speed of 500 rpm for 45 min at room temperature to obtain a high-transmittance coating solution; the components in the high-transmittance coating solution include, by mass:
[0060] 15 parts of magnesium fluoride powder, 1 part of zinc fluoride powder, 2 parts of zinc nitrate, 0.5 parts of sodium silicate, 1 part of polyethylene glycol (PEG-400) and 100 parts of 70% by volume ethanol solution;
[0061] (3) Spin coating the high-transmittance coating liquid onto the cleaned glass substrate surface at a spin coating speed of 850 rpm; then vacuum drying at 200° C. for 45 min to obtain a high-transmittance coating with a thickness of 200 nm;
[0062] (4) A micro-nanostructure array is formed on the surface of the high-transmittance coating by laser etching process; the laser energy density of the laser etching is 20 J / cm 2 , the repetition frequency is 600f / kHz, and the number of scans is 20 times; the shape of the micro-nanostructure in the micro-nanostructure array is pyramid-shaped, with a bottom side length of 100nm, a height of 100nm, and a spacing between adjacent micro-nanostructures of 200nm.
[0063] Comparative Example 2:
[0064] A high-transmittance self-cleaning coated glass comprises a glass substrate and a high-transmittance coated film attached to the surface of the glass substrate; wherein the glass substrate is commercially available silicate glass with a thickness of 1 cm.
[0065] The high-transmittance self-cleaning coated glass in this comparative example is prepared by the following steps:
[0066] (1) The glass substrate was rinsed with acetone and anhydrous ethanol in sequence, then rinsed with clean water, and then dried at room temperature;
[0067] (2) Adding magnesium fluoride powder (≤100 nm), titanium dioxide powder (≤100 nm), zinc fluoride powder (≤100 nm), zinc nitrate, sodium silicate and polyethylene glycol (PEG-400) in a formula amount to a 70% ethanol solution, stirring at a speed of 500 rpm for 45 min at room temperature to obtain a high-transmittance coating solution; the components in the high-transmittance coating solution include, by mass:
[0068] 15 parts of titanium dioxide powder, 1 part of zinc fluoride powder, 2 parts of zinc nitrate, 0.5 parts of sodium silicate, 1 part of polyethylene glycol (PEG-400) and 100 parts of 70% by volume ethanol solution;
[0069] (3) Spin coating the high-transmittance coating liquid onto the cleaned glass substrate surface at a spin coating speed of 850 rpm; then vacuum drying at 200° C. for 45 min to obtain a high-transmittance coating with a thickness of 200 nm;
[0070] (4) A micro-nanostructure array is formed on the surface of the high-transmittance coating by laser etching process; the laser energy density of the laser etching is 20 J / cm 2, the repetition frequency is 600f / kHz, and the number of scans is 20 times; the shape of the micro-nanostructure in the micro-nanostructure array is pyramid-shaped, with a bottom side length of 100nm, a height of 100nm, and a spacing between adjacent micro-nanostructures of 200nm.
[0071] Comparative Example 3:
[0072] A high-transmittance self-cleaning coated glass comprises a glass substrate and a high-transmittance coated film attached to the surface of the glass substrate; wherein the glass substrate is commercially available silicate glass with a thickness of 1 cm.
[0073] The high-transmittance self-cleaning coated glass in this comparative example is prepared by the following steps:
[0074] (1) The glass substrate was rinsed with acetone and anhydrous ethanol in sequence, then rinsed with clean water, and then dried at room temperature;
[0075] (2) Adding magnesium fluoride powder (≤100 nm), titanium dioxide powder (≤100 nm), zinc fluoride powder (≤100 nm), zinc nitrate, sodium silicate and polyethylene glycol (PEG-400) in a formula amount to a 70% ethanol solution, stirring at a speed of 500 rpm for 45 min at room temperature to obtain a high-transmittance coating solution; the components in the high-transmittance coating solution include, by mass:
[0076] 13 parts of magnesium fluoride powder, 3 parts of titanium dioxide powder, 2 parts of zinc nitrate, 0.5 parts of sodium silicate, 1 part of polyethylene glycol (PEG-400) and 100 parts of 70% by volume ethanol solution;
[0077] (3) Spin coating the high-transmittance coating liquid onto the cleaned glass substrate surface at a spin coating speed of 850 rpm; then vacuum drying at 200° C. for 45 min to obtain a high-transmittance coating with a thickness of 200 nm;
[0078] (4) A micro-nanostructure array is formed on the surface of the high-transmittance coating by laser etching process; the laser energy density of the laser etching is 20 J / cm 2 , the repetition frequency is 600f / kHz, and the number of scans is 20 times; the shape of the micro-nanostructure in the micro-nanostructure array is pyramid-shaped, with a bottom side length of 100nm, a height of 100nm, and a spacing between adjacent micro-nanostructures of 200nm.
[0079] Comparative Example 4:
[0080] A high-transmittance self-cleaning coated glass comprises a glass substrate and a high-transmittance coated film attached to the surface of the glass substrate; wherein the glass substrate is commercially available silicate glass with a thickness of 1 cm.
[0081] The high-transmittance self-cleaning coated glass in this comparative example is prepared by the following steps:
[0082] (1) The glass substrate was rinsed with acetone and anhydrous ethanol in sequence, then rinsed with clean water, and then dried at room temperature;
[0083] (2) Adding magnesium fluoride powder (≤100 nm), titanium dioxide powder (≤100 nm), zinc fluoride powder (≤100 nm), zinc nitrate, sodium silicate and polyethylene glycol (PEG-400) in a formula amount to a 70% ethanol solution, stirring at a speed of 500 rpm for 45 min at room temperature to obtain a high-transmittance coating solution; the components in the high-transmittance coating solution include, by mass:
[0084] 12 parts of magnesium fluoride powder, 1 part of zinc fluoride powder, 0.5 parts of sodium silicate, 1 part of polyethylene glycol (PEG-400) and 100 parts of 70% by volume ethanol solution;
[0085] (3) Spin coating the high-transmittance coating liquid onto the cleaned glass substrate surface at a spin coating speed of 850 rpm; then vacuum drying at 200° C. for 45 min to obtain a high-transmittance coating with a thickness of 200 nm;
[0086] (4) A micro-nanostructure array is formed on the surface of the high-transmittance coating by laser etching process; the laser energy density of the laser etching is 20 J / cm 2 , the repetition frequency is 600f / kHz, and the number of scans is 20 times; the shape of the micro-nanostructure in the micro-nanostructure array is pyramid-shaped, with a bottom side length of 100nm, a height of 100nm, and a spacing between adjacent micro-nanostructures of 200nm.
[0087] Comparative Example 5:
[0088] A high-transmittance self-cleaning coated glass comprises a glass substrate and a high-transmittance coated film attached to the surface of the glass substrate; wherein the glass substrate is commercially available silicate glass with a thickness of 1 cm.
[0089] The high-transmittance self-cleaning coated glass in this comparative example is prepared by the following steps:
[0090] (1) The glass substrate was rinsed with acetone and anhydrous ethanol in sequence, then rinsed with clean water, and then dried at room temperature;
[0091] (2) Adding magnesium fluoride powder (≤100 nm), titanium dioxide powder (≤100 nm), zinc fluoride powder (≤100 nm), zinc nitrate, sodium silicate and polyethylene glycol (PEG-400) in a formula amount to a 70% ethanol solution, stirring at a speed of 500 rpm for 45 min at room temperature to obtain a high-transmittance coating solution; the components in the high-transmittance coating solution include, by mass:
[0092] 12 parts of magnesium fluoride powder, 3 parts of titanium dioxide powder, 1 part of zinc fluoride powder, 2 parts of zinc nitrate, 0.5 parts of sodium silicate, 1 part of polyethylene glycol (PEG-400) and 100 parts of 70% by volume ethanol solution;
[0093] (3) The high-transmittance coating liquid was spin-coated onto the cleaned glass substrate surface at a spin coating speed of 850 rpm; and then vacuum dried at a temperature of 200° C. for 45 minutes to obtain a high-transmittance coating with a thickness of 200 nm.
[0094] Experimental example:
[0095] 1. Light transmittance test
[0096] The light transmittance of the high-transmittance self-cleaning coated glass prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was tested by the method described in "Measurement Method for Light Transmittance of Architectural Glass" (GB / T 7106-2008). The results are shown in Table 1.
[0097] Table 1 Light transmittance of high-transmittance self-cleaning coated glass
[0098] Visible light transmittance (%) Example 1 91.2 Example 2 90.7 Example 3 91.0 Comparative Example 1 86.3 Comparative Example 2 80.5 Comparative Example 3 87.1 Comparative Example 4 84.4 Comparative Example 5 83.2
[0099] As can be seen from Table 1, the light transmittance of the high-transmittance self-cleaning coated glass prepared by the preparation process of the present invention (Examples 1 to 3) is above 90.5%, which has excellent light transmittance. The light transmittance of the high-transmittance self-cleaning coated glass in Comparative Examples 1 to 5 is significantly reduced, indicating that the composition of the high-transmittance coating (Comparative Examples 1 to 4) and the surface morphology of the high-transmittance coating (Comparative Example 5) can affect the light transmittance of the high-transmittance self-cleaning coated glass. Only by using a specific composition and surface morphology can a better light transmittance be achieved.
[0100] 2. Self-cleaning performance test
[0101] The high-transmittance self-cleaning coated glass prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was placed in an experimental room at an angle, and then oil smoke with dust was introduced into the room for 30 minutes each time, 6 times a day, and 4 hours between each time; then artificial rainfall was simulated every two days, and 1 hour each time. This lasted for a total of 1 month, and the pollution on the surface of the high-transmittance self-cleaning coated glass was observed. The results are shown in Table 2.
[0102] Table 2 Pollution of high-transmittance self-cleaning coated glass
[0103]
[0104]
[0105] As can be seen from Table 2, the high-transmittance self-cleaning coated glass prepared by the preparation process of the present invention (Examples 1 to 3) can effectively prevent stains from accumulating on the surface, has a good self-cleaning effect, and can be used for a long time without manual cleaning. However, the self-cleaning effect of the high-transmittance self-cleaning coated glass in Comparative Examples 1 to 5 is poor, indicating that the composition of the high-transmittance coating (Comparative Examples 1 to 4) and the surface morphology of the high-transmittance coating (Comparative Example 5) can affect the self-cleaning performance of the high-transmittance self-cleaning coated glass. Only by using a specific composition and surface morphology can a better self-cleaning effect be achieved.
[0106] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.
Claims
1. A high-transmittance self-cleaning coated glass, characterized in that: It comprises a glass substrate and a high-transmittance coating film attached to the surface of the glass substrate; the high-transmittance coating film is obtained by the following steps: S1: Prepare a high-transmittance coating solution, wherein the high-transmittance coating solution comprises the following components in parts by weight: 10-15 parts of magnesium fluoride powder, 2-4 parts of titanium dioxide powder, 0.5-2 parts of zinc fluoride powder, 1-3 parts of zinc salt, 0.2-1 parts of silicate, 0.5-2 parts of polyethylene glycol and 100 parts of solvent; S2: Spin coating the high-transmittance coating liquid onto the cleaned glass substrate surface by spin coating, with the spin coating speed being 800-1000 rpm; and then vacuum drying to obtain a high-transmittance coating with a thickness of 100-300 nm; S3: A micro-nano structure array is formed on the surface of the high-transmittance coating by using a laser etching process; the micro-nano structure is in the shape of a pyramid, a terrace or a cone.
2. The high-transmittance self-cleaning coated glass according to claim 1, characterized in that: The glass substrate is commercially available silicate glass or commercially available borosilicate glass, and has a thickness of 0.5 to 2 cm.
3. The high-transmittance self-cleaning coated glass according to claim 1, characterized in that: The high-transmittance coating solution comprises the following components in parts by mass: 12 parts of magnesium fluoride powder, 3 parts of titanium dioxide powder, 1 part of zinc fluoride powder, 2 parts of zinc salt, 0.5 parts of silicate, 1 part of polyethylene glycol and 100 parts of solvent.
4. The high-transmittance self-cleaning coated glass according to claim 1, characterized in that: The preparation of the high-transmittance coating solution comprises the following steps: adding a formula amount of magnesium fluoride powder, titanium dioxide powder, zinc fluoride powder, zinc salt, silicate and polyethylene glycol into a solvent, and stirring for 30 to 60 minutes to obtain the solution.
5. The high-transmittance self-cleaning coated glass according to claim 1, 3 or 4, characterized in that: The particle sizes of the magnesium fluoride powder, titanium dioxide powder and zinc fluoride powder are all less than 100 nm.
6. The high-transmittance self-cleaning coated glass according to claim 1, 3 or 4, characterized in that: The silicate is sodium silicate or potassium silicate; the zinc salt is zinc nitrate or zinc chloride; and the solvent is an ethanol solution with a volume fraction of 70%.
7. The high-transmittance self-cleaning coated glass according to claim 1, characterized in that: In S2, the spin coating speed is 850 rpm; the vacuum drying temperature is 180-220° C., and the drying time is 30-60 min.
8. The high-transmittance self-cleaning coated glass according to claim 1, characterized in that: The laser energy density of laser etching in S3 is 15~30J / cm 2 , the repetition frequency is 500-700f / kHz, and the number of scans is 15-30 times.
9. The high-transmittance self-cleaning coated glass according to claim 1, characterized in that: The spacing between adjacent micro-nano structures in the micro-nano structure array is 100-200 nm, and the height of the micro-nano structure is 50-200 nm.
10. The method for preparing the high-transmittance self-cleaning coated glass according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Cleaning the glass substrate; (2) preparing a high-transmittance coating liquid, and applying the high-transmittance coating liquid to the surface of the cleaned glass substrate by spin coating; and then vacuum drying to obtain a high-transmittance coating with a thickness of 100 to 300 nm; (3) A micro-nano structure array is formed on the surface of the high-transmittance coating using a laser etching process.